Efecto de la cobertura de quitosano y aceite esencial de canela en la conservación de fresa (fragaria ananassa) var. Aroma, mínimamente procesada - Zavaleta Garcia, Nancy Magaly (2017)
The objective of this work was to determine the coverage effect of chitosan and essential oil of cinnamon in the phenolic content, antioxidant capacity, mold and yeast counts and general acceptability in minimally processed strawberry for 1, 4, 7, 10, 13 and 16 days of refrigerated storage at 10°C. For this purpose the experimental design comprised a response surface methodology using a Rotational Central Composite Design (RCCD). The variable ranges used were 0.7 – 2% (Chitosan) and 0.02 – 0.1% (cinnamon essential oil). It was found that the significated variable (p<0.05) was the essential oil of cinnamon (L and Q) for phenols content and antioxidant capacity at a concentration of 0.001 gmL-1 which was most effective during the first days of storage, characteristic that tends to decrease throughout the study. It was also found that both independent variables significantly influence (p<0.05) the decrease of microbial load. Finally, the use of coverage of chitosan and essential oil of cinnamon does not affect its sensory acceptability and helps to maintain the shelf life of minimally processed strawberry.